MEMAHAMI HUKUM ISLAM DALAM PENAFSIRAN ALQURAN MELALUI QAIDAH BAHASA ARAB - Nasution, Ahmad Bangun (State of Islamic Institute Langsa, 2018)
The Qur'an as a guidance for all mankind must be upheld and carried out. The content of the Qur'an has several teachings of life so that a servant will find the happiness in the world and especially in the hereafter. The Qur'an is like an amazing ocean and its uniqueness has never been swallowed up by the times, so the various interpretations emerged with various methods as well. The tafsir books that fulfill the library is a proof of how excited and attentive the scholars in understanding the meanings as well as the messages contained in the Qur'an.